Connections between Internal and Surface properties of Massive Stars - Farrell, Eoin James (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
Massive stars have an important impact on the universe. They are responsible for the generation of many of the chemical elements such as oxygen and silicon. They can produce core collapse supernovae which impact the chemical enrichment of the interstellar medium and galaxies, triggering of star formation and release of energy into the surroundings. They also produce neutron stars and black holes which can merge in binary systems and emit detectable gravitational waves. The evolution of massive stars is affected by a variety of physical processes including convection, rotation, mass loss and binary interaction. Because these processes modify the internal chemical abundance profiles in multiple ways simultaneously, it can be challenging to connect the properties of the internal abundance profile to the location in the HR diagram. We developed a new stellar modelling approach called snapshot that allows us to systematically compute stellar structure models in hydrostatic and thermal equilibrium. Using our approach, we computed numerical stellar structure models in thermal equilibrium covering key phases of stellar evolution. We applied our snapshot method to explore several topics. We first studied the properties of red supergiants and of stars stripped of their envelopes in binary systems and constrained the mass of one of these stripped stars in a binary system, HD 45166. Second, we investigated the connections between the surface properties and the masses of progenitors of core collapse supernovae and direct collapse black holes. Finally, we constructed a series of numerical experiments to isolate the key features of the internal abundance profile that drive the evolution of massive stars. We discussed why massive stars expand after the main sequence and the fundamental reasons for why they become red, blue or yellow supergiants. We also conducted several other investigations into other aspects of stellar evolution. Following the observation of a surprisingly massive 85 solar mass black hole in the binary black hole merger GW190521 by the LIGO Virgo Collaboration, we investigated whether such a black hole could be produced by the first stellar generations. Our models suggested the possibility of black hole masses of up to 75 solar masses, but uncertainties related to convective mixing, mass loss, H-He shell interactions and pair-instability pulsations could increase this limit to 85 solar masses. Secondly, we investigated the impact of binary interaction on the evolution of blue supergiants and how this affects the use of these stars for distance determination. Finally, we combined observations with theoretical models of magnetic field evolution to infer the initial distribution of magnetic fields for 1.4 - 3.4 solar masses AB stars. We inferred an initial field distribution with a mean of ≥800 G and a width of ≥600 G.
APPROVED